2010
DOI: 10.1099/ijs.0.013300-0
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella xiamenensis sp. nov., isolated from coastal sea sediment

Abstract: A Gram-negative, motile, rod-shaped bacterium, strain S4 T , was isolated from coastal sediment collected off Xiamen, China. The physiological and biochemical features of strain S4 T , determined using the API 20NE, API ZYM and Biolog GN2 systems, were similar to those of members of the genus Shewanella. Phylogenetic analyses based on 16S rRNA and gyrB gene sequences placed strain S4 T in the genus Shewanella, and it was most closely related to Shewanella oneidensis and related species. DNA-DNA hybridization d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 24 publications
(26 reference statements)
1
44
0
1
Order By: Relevance
“…Biochemical characteristics (Table 2) of WCJ25 were determined using the API 20E and 20NE systems (bioMérieux). Strain WCJ25 exhibited a biochemical pattern similar to that of S. xiamenensis type strain S4 (Huang et al, 2010), except that WCJ25 did not utilize glucose, arabinose and caprate (Table 2). WCJ25 was susceptible to amikacin, gentamicin, tobramycin, cefotetan, imipenem, trimethoprim/sulphamethoxazole, levofloxacin, showed intermediate resistance to piperacillin/tazobactam and ciprofloxacin, and resistant to azithromycin, ampicillin, ampicillin-sulbactam, ceftazidime, cefepime, ceftriaxone and ceftizoxime.…”
Section: Case Reportmentioning
confidence: 96%
See 2 more Smart Citations
“…Biochemical characteristics (Table 2) of WCJ25 were determined using the API 20E and 20NE systems (bioMérieux). Strain WCJ25 exhibited a biochemical pattern similar to that of S. xiamenensis type strain S4 (Huang et al, 2010), except that WCJ25 did not utilize glucose, arabinose and caprate (Table 2). WCJ25 was susceptible to amikacin, gentamicin, tobramycin, cefotetan, imipenem, trimethoprim/sulphamethoxazole, levofloxacin, showed intermediate resistance to piperacillin/tazobactam and ciprofloxacin, and resistant to azithromycin, ampicillin, ampicillin-sulbactam, ceftazidime, cefepime, ceftriaxone and ceftizoxime.…”
Section: Case Reportmentioning
confidence: 96%
“…Shewanella xiamenensis is a newly established species of the genus Shewanella; the type strain of this species was found in costal sea sediments off Xiamen, Fujian province, China (Huang et al, 2010). Although Shewanella species, especially Shewanella algae and Shewanella putrefaciens, have been recognized as human pathogens, there appear to have been no reports of the isolation of S. xiamenensis from any clinical samples and this species has not previously been documented as a cause of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the MR-1 wild type and its mutants omcA and mtrC were still capable of reducing Au 3+ into Au@NPs (Wu et al 2013b), while the particle size of the extracellular nanoparticles were decreased mtrC and omcA mutants (Ng et al 2013). On the other hand, Shewanella xiamenensis, which is isolated from coastal sediment collected off Xiamen, China, is a close-related strain to S. oneidensis based on phylogenetic tree analysis by 16S rRNA and gyrase gene (Huang et al 2010). It has also been reported to reduce mediators from the medium to nanoparticles (Ng et al 2015a) and also showed resistance to different kinds of metal ions (Ng et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Exiguobacterium oxidotolerans has been isolated from a drain in a fish processing plant in Hokkaido (Yumoto et al 2004) and from sea mud (Chen et al 2010). Shewanella xiamenensis has been isolated from sea floor sediment (Ng et al 2014;Huang et al 2010). These three species of bacteria are present on the sea floor where shrimp live, so it was not surprising to encounter them in our samples.…”
Section: Bacterial Degradation Of Ampmentioning
confidence: 99%